Callochiton Gray 1847 ... - Sirenko, Boris I.; Zhang, Junlong (Zenodo, 2019)
Genus Callochiton Gray, 1847 Type species. Chiton laevis Montagu, 1803, non Pennant, 1777 (= Chiton septemvalvis Montagu, 1803), SD Gray 1847. Genus distribution and range. NE Atlantic Ocean, Indian Ocean, West Pacific Ocean from Japan to Australia and New Zealand, SE Pacific, Antarctica. Miocene-Recent. ... : Published as part of Sirenko, Boris I. & Zhang, Junlong, 2019, Chitons (Mollusca: Polyplacophora) of Hainan Island and vicinity, South China Sea, pp. 1-40 in Zootaxa 4564 (1) on page 4, DOI: 10.11646/zootaxa.4564.1.1, http://zenodo.org/record/2588445 ...